General Principles and Challenges of Public Administration Organization in Germany - Szirbik , Miklós; Küpper, Herbert; Anderheiden , Michael (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
Germany has a federal system. Most legislation is enacted at the federal level, whereas federal units, the Länder (singular: Land), are responsible for the execution of federal and Länder laws. Consequently, most public administration organizations are operated by the Länder. Most Länder organize their administration at three levels: the local level, where both state organs and autonomous local governments operate; the mid-level, with a concentration of state tasks in a centralised mid-level authority (the so-called province); and the state level, where ministries exercise political leadership and supreme Land authorities perform administrative tasks. Local governments do not only perform the tasks related to local autonomy, as defined in German as the ‘affairs of the local community’, but are also the recipients of delegated first-instance state tasks. Owing to local governments’ autonomy, the Länder authorities are limited to overseeing the legality and must refrain from assessing the expediency of such measures in the field of the affairs of the local community. Länder play a more significant role in supervising the performance of delegated state tasks because, in this field, they may control local authorities in terms of legality as well as expediency. Balancing the correct level of oversight without infringing on local autonomy is often a delicate process. Apart from the territory-bound autonomy of local governments, Germany is rich in other forms of autonomous administrative units, such as chambers and universities. Administrative infrastructure at the federal level is limited to ministries and supreme federal authorities. The Federation operates a full administrative apparatus in very few cases, such as for the armed forces, diplomatic service, or federal police. In all other fields of public administration, administrative functions are performed by Länder organs. When they execute federal law, the supreme federal authorities exercise supervision over legality and, in rare cases, when statutes authorise them to do so, supervision over expediency. We describe and analyse the structure of the German Länder administration using the Land of Baden-Württemberg as an example.KEYWORDS Germany, public administration, administrative federalism, local government, LänderBibliographyBaden-Württemberg  Ministry  of  Finance  (2023)  ‘Beteiligungen  und  Landesbetriebe  im Überblick‘, Baden-Württemberg Ministerium für Finanzen [Online]. Available at: https://fm.baden-wuerttemberg.de/de/bauen-beteiligungen/unternehmen-und-beteiligungen/unternehmen-im-ueberblick (Accessed: 6 November 2023).Bogumil,  J.,  Holtkamp,  L.  (2013)  Kommunalpolitik  und  Kommunalverwaltung.  Eine  praxisorientierte Einführung. Bonn: Bundeszentrale für politische Bildung.Hellermann, J. (2023) ‘Artikel 28 [Verfassung der Länder]’ in Epping, V., Hillgruber, C. (eds.) Beck’scher Online-Kommentar Grundgesetz. 54th edn. München: C. H. Beck.Klus, S. (2013) Die europäische Stadt unter Privatisierungsdruck. Konflikte um den Verkauf kommunaler  Wohnungsbestände  in  Freiburg.  Wiesbaden:  Springer;  https://doi.org/10.1007/978-3-658-02449-9.Landkreistag  Baden-Württemberg  (2023)  ‘Die  Landkreise  in  Baden-Württemberg‘,  Baden-Württemberg [Online]. Available at: https://www.landkreistag-bw.de/index.php?id=62 (Accessed 6 November 2023).Radbruch, G. (1946) ‘Gesetzliches Unrecht und übergesetzliches Recht’, Süddeutsche Juristenzeitung, 1, pp. 105–108.Sachs, M. (2018) Grundgesetz Kommentar. 8th edn. München: C.H. Beck.Sachs, M. (2018) Grundgesetz Kommentar. 8th edn. München: C.H. Beck.